1998
DOI: 10.1080/00016349808565806
|View full text |Cite
|
Sign up to set email alerts
|

The significance of birth weight difference in discordant twins: a level to standardize?

Abstract: We postulate that definition of discordant growth in twin gestations should be categorized with respect to gestational week since the level of discordance prejudicing fetal or neonatal jeopardy may vary in different stages of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 0 publications
0
11
0
7
Order By: Relevance
“…A further perinatal study with a large number of twin pregnancies, (except twin-twin transfusion syndromes, including early intrauterine death or stillbirths) should investigate for maternal problems, perinatal outcomes, intrapartum or postpartum deaths and other complications in discordant twins. A study on discordant twins concluded that the definition of discordant growth in twin gestations should be categorized with respect to gestational age since the level of discordance may have differing effects on neonatal morbidity and mortality depending on the stage of pregnancy (Yalçin et al, 1998). Further studies should also compare gestational differences between discordant twins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further perinatal study with a large number of twin pregnancies, (except twin-twin transfusion syndromes, including early intrauterine death or stillbirths) should investigate for maternal problems, perinatal outcomes, intrapartum or postpartum deaths and other complications in discordant twins. A study on discordant twins concluded that the definition of discordant growth in twin gestations should be categorized with respect to gestational age since the level of discordance may have differing effects on neonatal morbidity and mortality depending on the stage of pregnancy (Yalçin et al, 1998). Further studies should also compare gestational differences between discordant twins.…”
Section: Discussionmentioning
confidence: 99%
“…Early neonatal mortality was defined as mortality in the first week of life which is related to perinatal factors rather than neonatal mortality. Birthweight discordance was calculated by subtracting the birthweight of the smaller twin from the weight of the larger twin, and dividing the difference by the birthweight of the larger twin and multiplying that by 100 (Yalçin et al, 1998).…”
Section: Subjectsmentioning
confidence: 99%
“…Some studies (Cheung et al, 1995;Fraser et al, 1994;Rydhstrom, 1994;Talbot et al, 1997;Yalcin et al, 1998) report an association between birthweight discordance and fetal/infant death. In contrast to these findings, several studies challenge the clinical importance of birthweight discordance and argue that the actual birthweight of each twin within the pair, rather than the difference between the twins, is the most important determinant of outcome (Fraser et al, 1994;Talbot et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Yalcin et al (1998) showed that the effect of birthweight discordance may differ according to GA. Several investigators have restricted their analyses of discordance to either preterm or term gestations (Cheung et al, 1995;Talbot et al, 1997). Demissie et al (2002) performed analyses after stratifying the data by GA categories (17-31, 32-36 and 37-41 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] The design of our study does not allow to draw these definitive conclusions on the effect of laser therapy on fetal growth. These changes in fetal growth could also have occurred in a control group without laser therapy.…”
Section: Methodsmentioning
confidence: 99%